A Christmas too big - Madden, Colleen M. (New York Two Lions, 2021)
Kerry's family goes berserk with Christmas every year, but Kerry needs a little peace and quiet. Her neighbor, Mrs. Flores, is having a quieter Christmas, with decorations and music from the country where she used to live.
In English and Spanish.
111084
Keywords: Families -- Juvenile fiction; Hispanic Americans -- Juvenile fiction; Christmas stories; Christmas decorations -- Juvenile fiction; Picture books for children; Fiction; Christmas fiction